Pendampingan Digitalisasi Arsip, Penataan Kelengkapan Dokumen dan Sosialisasi Pemasaran Produk BUMDes di Desa Rogodono, Kecamatan Buayan, Kabupaten Kebumen - Tiyan Fatkhurrokhman; Shafitri Nire Pangestika; Riski yudhi Prasongko; , Hanni Rahma Junaedi; Rochmah Tri Alfiyah; Rasya Nabil Annafi (Institut Teknologi dan Bisnis Semarang, 2026)
This community service program aims to assist Rogodono Village-Owned Enterprise (BUMDes) in Buayan District, Kebumen Regency, in digitalizing physical archives, organizing document completeness, and promoting its products through digital marketing. The background of this activity is the limited archiving system of BUMDes, which still relies on printed documents that are difficult to search, duplicate, and are vulnerable to damage, as well as the low utilization of digital media for product marketing. The method used includes a participatory approach through document identification, scanning and digital filing, document completeness verification, and marketing socialization training for the BUMDes management. The results show that all identified physical documents have been converted into digital format and systematically organized, the completeness of BUMDes legal and administrative documents has improved, and the management gained new knowledge and skills in promoting BUMDes products through digital platforms. This activity is expected to strengthen administrative order, data security, and product competitiveness of Rogodono BUMDes, and to serve as a model for similar community service activities in other villages.